Comparing the Effects of Ethyl Elcoholic and Aquatic Extracts and Alkaline Compounds of Some Plants on the Bioefficacy of Culex pipiens (Diptera:Culicidae) - Saady, Rabah Hassan; Mansoor, Abdulrahman Jihad (Iraqi Journal of Science, 2021)
The results of the present study show the biological effects of ethyl elcoholic and aquatic extracts as well as alkaloids compounds of Atriplex helmius and Capparis spinosa roots. The results demonstrated the superiority of the cold aqueous extract of C. capparis at the highest concentration of 20 mg / ml, as the killing rate was 81.16% for the second larval instar of Cx. pipiens after 72 hours of exposure. While, the killing rate caused by the same treatment was 79.52% for the third larval instar. The results also showed the superiority of the alcoholic extract against C. spinosa , as the killing rate reached 98.55% for the second larval instar after 72 hours of treatment at a concentration of 20 mg/ml. As for A. halmius extract, the same treatment caused the lowest killing rate of 89.27% ​​ for the third instar of Cx. pipiens. The study also showed significant effects of the raw alkaline compounds’ extracts of A. halimus roots on the killing of non-adult instars of Cx. pipiens L. The highest rate of mortality observed was 88.54% at the highest concentration of 20 mg /ml at the second instar. Also, significant effects of raw alkaline compounds’ extracts of C. spinosa roots were observed. The highest mortality was 69.21% at the highest concentration of 20 mg/ml for the third larval instar,